Do Rural Banks Matter? Evidence from the Indian Social Banking Experiment - Burgess, Robin; Pande, Rohini (American Economic Review, 2005)
Lack of access to finance is often cited as a key reason for why poor people remain poor. This paper uses data on the Indian rural branch expansion program to provide empirical evidence on this issue. Between 1977 and 1990, the Indian central bank mandated that a commercial bank can open a branch in a location with one or more bank branches only if it opens four locations with no bank branches. We show that, between 1977 and 1990, this rule caused banks to open relatively more rural branches in Indian states with lower initial financial development. The reverse was true outside this period. We exploit this fact to identify the impact of opening a rural bank on poverty and output. Our estimates suggest that the Indian rural branch expansion program significantly lowered rural poverty, and increased non-agricultural output.